Temporal changes in treatment patterns by age group and functional status before and after PD-1/L1 inhibitor approvals in advanced urothelial carcinoma - Doshi, Gurjyot K.; Li, Haojie; Burcu, Mehmet; Annavarapu, Srinivas; Wells, Karen; Imai, Kentaro; Moreno, Blanca Homet; Singhal, Puneet; Mamtani, Ronac (Frontiers in Oncology, 2023)
Metastatic urothelial carcinoma (mUC) has poor prognosis. A high unmet need exists for novel treatment for those who are unfit for platinum-based chemotherapy. We aimed to describe real-world temporal changes in patient characteristics and 1L treatment selection for mUC patients in the United States following the approval of anti-PD-1/L1 treatments.After approval of 1L anti-PD-1/L1 treatment for mUC, there is a marked increase in the use of 1L anti-PD-1/L1 monotherapies, accompanied by a proportional decrease in 1L platinum-based treatments and non-guideline-based therapy; particularly among the elderly (> 75 years) and those with poor ECOG performance status (ECOG PS 2+). Anti-PD-1/L1 monotherapies fulfill the prior unmet need of frail mUC patients who are ineligible for platinum-based therapies.